Study on Techniques to Defend Against Social Network Sybils - Rajeswari S, Mrs.; Priya C, Keerthi; P, Nikitha (IJRDO -Journal of Computer Science Engineering, 2016)
Unscrupulous users increasingly findOnline Social Networking (OSN) platforms aslucrative targets for malicious activities, such assending spam and spreading malware. Theprofitability of such activities and the fact that a largeportion of the OSN communication takes place oversocial links (e.g., Facebook) that are symmetric innature, motivate attackers to connect to real users. Inparticular, attackers take advantage of the opennature of OSNs and send to legitimate users unwantedfriend requests, also known as friend spam.Thesefriend spams have proven to be among the mostevasive malicious activities